2014
DOI: 10.1080/19443994.2013.841102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stirring strategies on the sludge granulation in anaerobic CSTR reactor

Abstract: A B S T R A C TThe anaerobic sludge granulation was studied in two laboratory-scale continuous-flow stirred tank reactors (CSTRs), which treating synthetic glucose wastewaters under a mesophilic constant temperature of 35 ± 1˚C. Different stirring strategies were employed in the two CSTRs. Magnetic stirring at a rotation speed of 140 rpm was used in CSTR1 and axial continuous agitation at a speed of 90 rpm in CSTR2. It was observed that highly activated granular sludge formed in CSTR2, but flocculent sludge st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, granulation is not common in continuously stirred reactors as nearly all granular sludge types are produced in column-type or liquid-upflow reactors or sequencing batch reactors [16]. On the other hand, other authors have also reported granulation in continuous stirred reactors [17] [18] and some concluded that also axial flow-mixing can have a positive effect on sludge granulation [19]. did not report granulation in a similar chain elongation study using an upflow anaerobic filter with the same process conditions (T = 30 °C, pH = 6.8, HRT = 17 h) and with the same influent composition (synthetic medium containing propionate and 8 ethanol) [20].…”
Section: Granulation and Sludge Retentionmentioning
confidence: 95%
“…However, granulation is not common in continuously stirred reactors as nearly all granular sludge types are produced in column-type or liquid-upflow reactors or sequencing batch reactors [16]. On the other hand, other authors have also reported granulation in continuous stirred reactors [17] [18] and some concluded that also axial flow-mixing can have a positive effect on sludge granulation [19]. did not report granulation in a similar chain elongation study using an upflow anaerobic filter with the same process conditions (T = 30 °C, pH = 6.8, HRT = 17 h) and with the same influent composition (synthetic medium containing propionate and 8 ethanol) [20].…”
Section: Granulation and Sludge Retentionmentioning
confidence: 95%
“…Biohydrogen production from activated sludge through anaerobic fermentation has unique advantages of high ecological adaptability, simple reaction conditions and low nutrient requirements [5,6], which have been extensively researched worldwide. The Continuous Stirred Tank Reactors (CSTR) is one of the most commonly used anaerobic reactors both in engineering applications and in experimental studies, it is equipped with a magnetic stirrer, which can keep the microorganisms of the anaerobic sludge in suspension by adjusting the stirring rate, and the biochemical reaction rate increases with the increase in the impeller rotation rate [7,8]. However, the suspended microorganisms are influenced by the increase in the hydraulic load applied by the rotating impeller; therefore, sludge is easily washed out [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, granulation is not common in continuously stirred reactors as nearly all granular sludge types are produced in column-type or liquid-up ow reactors or sequencing batch reactors [44]. On the other hand, other authors have also reported granulation in continuous stirred reactors [45] [46] and some concluded that also axial ow-mixing can have a positive e ect on sludge granulation [47]. Grootscholten et al (2013) did not report granulation in a similar chain elongation study using an up ow anaerobic lter with the same process conditions (T = 30 °C, pH = 6.8, HRT = 17 h) and with the same in uent composition (synthetic medium containing propionate and ethanol) [26].…”
Section: Granulation and Sludge Retentionmentioning
confidence: 99%